Profile of anxiolytic consumption by patients seen in a basic pharmacy - Diniz, Vânia Maria de Carvalho (2022)
Introduction: Mental disorders are more and more frequent. In Brazil, primary care makes possible the population's first encounter with mental care, having medicines as one of the main therapeutic applied resources, which are made available in different ways, including the municipal primary pharmacy. Psychotropic drugs, such as anxiolytics, act on these mental disorders, improving the quality of life and providing freedom to the individual, however, their use irrationally and for a prolonged period of time causes harm to those who use them. Objective: To know the aspects surrounding the consumption of anxiolytic drugs, as well as to identify individual and collective characteristics of the participants that lead to their use. Methodology: Cross-sectional descriptive research with a quali-quantitative approach, carried out with prescriptions that contained anxiolytics and questionnaires answered by patients treated at the basic pharmacy in the city of Flores - PE. Results: The female gender, age group over 41 years, low education, presence of children and marriage were related to the increase in the use of anxiolytics, in addition, the emergence of effects caused by treatment abandonment, interactions regarding the use of plants or more of a drug with anxiolytics and the errors of gifts in prescriptions had high rates. Conclusion: The delineation of the profile of individuals who use anxiolytics as therapy provides the creation of policies at specific groups in order to reduce the therapy with them, in addition, knowledge of the main errors in prescriptions and the presence of interactions ensures a better treatment success.